Herpetofauna from a protected area situated in a biogeographic transition zone in Central South America - Dorado-Rodrigues, Tainá Figueras; Valadão, Rafael Martins; Valério, Luciana Mendes [UNESP]; de Castro, Carolina Potter; Strüssmann, Christine (FapUNIFESP (SciELO), 2025)
Several herpetofaunal inventories have been conducted in the Neotropical region. However, many areas remain to be investigated, and this is particularly true of transition zones between distinct ecoregions. Herein we describe the richness, species composition, and abundance of herpetofauna from a scarcely known portion of the Brazilian Cerrado and assess the taxonomic similarities of the assemblages among the sampled habitats and between neighbouring ecoregions. A mid-term herpetological inventory was conducted from May 2009 to January 2011 at Serra das Araras Ecological Station (SAES) using pitfall traps with drift fences in five distinct forested and open habitats. In these and in additional habitats, visual and acoustic searches and occasional encounters were also used to access the local composition of the herpetofauna, together with literature data and examination of specimens deposited in collections. We also compared the species composition at SAES on a regional scale with those of other 29 localities previously studied in nine South American ecoregions. We documented 123 species at the SAES (39 amphibians and 84 reptiles), 112 of which were recorded during the field inventory. Richness was highest in riparian forests and lowest in semi-deciduous dry forest and cerrado woodland. Riparian forests also presented the highest number of exclusive species, while only one exclusive species was found in cerrado woodland. Cerrado sensu stricto and cerrado parkland contained 53 and 40 species, including seven and 10 exclusive species, respectively, and showed greater similarity than the sampled forested habitats. In comparison to other localities in the Cerrado (including transition zones), SAES is home to one of the most diverse assemblages of herpetofauna. This may be attributed to continued sampling efforts and to the marked environmental heterogeneity resulting from the topographic profile and confluence of several ecoregions. Amphibian species composition at SAES is more similar to a nearby locality also studied in the Cerrado and to Chiquitano Dry Forest assemblages, while the reptile species composition is nested among the assemblages studied in the Cerrado. Our findings indicate that the herpetofauna of SAES is rich and representative of the regional biodiversity, with species composition evidencing its transitional character.
Herpetofauna de uma área protegida situada em zona de transição na porção central da América do Sul
Keywords: Anura; biodiversity; Brazilian savanna; ecotone; Reptilia